The universe below : - Broad, William J. (Simon & Schuster, 1997)
Broad takes us on breathtaking dives and expeditions - to the Azores, to the Titanic, to hot springs teeming with bizarre life, to icy fissures aswarm with gulper eels, vampire squids, and gelatinous beasts longer than a city bus. We meet legendary explorers at the forefront of deep research and go with them as they probe the ancient mysteries of the deep. This universe below encompasses the vast majority of the Earth's habitable space and nurtures perhaps ten times as many species of life as are known on land. Broad shows that the abyss also holds millions of humanity's lost artworks and treasures - more than all the world's museums combined. Yet, remarkably, human eyes up to now have glimpsed perhaps only a billionth of this unfamiliar realm, a place of crushing pressure and eternal darkness."